Historians and the Law in Postrevolutionary France - DONALD R. KELLEY (Princeton University Press, 2014)
This is an essay in a rather specialized area of intellectual history, but it touches on larger concerns. One is the familiar point, argued and illustrated a generation and more ago by Herbert Butterfield and before him Lord Acton, that the history of historiography is more than an exercise in hagiography, a trivial version of the "Whig fallacy"; it is also a path to cultural self-criticism and self-understanding.1 Of all scholars, historians should be least susceptible to that academic "amnesia" lamented by Sorokin that leads each generation to invent the wheel anew, to claim a novelty that on reflection turns out to be an old construct given a new dress.2 Yet fashion and generational divergence seem to affect historiography almost as immediately as they have philosophy or literary criticism, despite irrepressible "scientific" claims. How many faces has Clio shown us over the centuries? How many "new histories" have there been since La Popeliniere's project of 1599? The claims have been many, and consistently grandiose. Not superficial events but deep structures of society, Annalistes have argued; not drums and trumpets but the life of the people, J. R. Green proclaimed; not just religion and politics but all of civilization, Voltaire pleaded, as James Harvey Robinson has done in our century.3 In this book we encounter still another histoire nouvelle, whose novelty was likewise defined in invidious contrast to a prevailing style of historical writing perceived as narrow and inadequate. As with the other "new histories," however, we have paid too much attention to the rhetoric and the pretensions of the conspicuous figures and not enough to the practice and accomplishments of their less visible or less fashionable colleagues. My first purpose is to take a closer look at this seminal period of historical scholarship, roughly the two generations between 1804 and 1848, and so to gain a better general perspective on the history of history.